SARS-CoV-2 infection dysregulates NAD metabolism - Izadpanah, Amin; Mudd, Joseph C.; Garcia, Joe G. N.; Srivastav, Sudesh; Abdel-Mohsen, Mohamed; Palmer, Clovis; Goldman, Aaron R.; Kolls, Jay K.; Qin, Xuebin; Rappaport, Jay (Frontiers in Immunology, 2023)
Severe COVID-19 results initially in pulmonary infection and inflammation. Symptoms can persist beyond the period of acute infection, and patients with Post-Acute Sequelae of COVID (PASC) often exhibit a variety of symptoms weeks or months following acute phase resolution including continued pulmonary dysfunction, fatigue, and neurocognitive abnormalities. We hypothesized that dysregulated NAD metabolism contributes to these abnormalities. RNA sequencing of lungs from transgenic mice expressing human ACE2 (K18-hACE2) challenged with SARS-CoV-2 revealed upregulation of NAD biosynthetic enzymes, including NAPRT1, NMNAT1, NAMPT, and IDO1 6 days post-infection. Our data also demonstrate increased gene expression of NAD consuming enzymes: PARP 9,10,14 and CD38. At the same time, SIRT1, a protein deacetylase (requiring NAD as a cofactor and involved in control of inflammation) is downregulated. We confirmed our findings by mining sequencing data from lungs of patients that died from SARS-CoV-2 infection. Our validated findings demonstrating increased NAD turnover in SARS-CoV-2 infection suggested that modulating NAD pathways may alter disease progression and may offer therapeutic benefits. Specifically, we hypothesized that treating K18-hACE2 mice with nicotinamide riboside (NR), a potent NAD precursor, may mitigate lethality and improve recovery from SARS-CoV-2 infection. We also tested the therapeutic potential of an anti- monomeric NAMPT antibody using the same infection model. Treatment with high dose anti-NAMPT antibody resulted in significantly decreased body weight compared to control, which was mitigated by combining HD anti-NAMPT antibody with NR. We observed a significant increase in lipid metabolites, including eicosadienoic acid, oleic acid, and palmitoyl carnitine in the low dose antibody + NR group. We also observed significantly increased nicotinamide related metabolites in NR treated animals. Our data suggest that infection perturbs NAD pathways, identify novel mechanisms that may explain some pathophysiology of CoVID-19 and suggest novel strategies for both treatment and prevention.